Utilization of Arjasa Village Community as a Quality Support of the Laboratory of Ushuluddin Adab and Humanities Faculty IAIN Jember - Mawardi Purbo Sanjoyo; Bernadien, Win Usuluddin; Firmansyah, Irfa' As'at (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
This study aims to develop laboratory functions on non-exact functions. Research locations for non-exact laboratory functions are outdoors or in the field. In this study, the development of non-exact laboratory functions is intended for the laboratory of the Faculty of Ushuluddin, Adab, and Humanities IAIN Jember. The location chosen is Arjasa Village which is currently developing into a Tourism Village. The focus of this research is (1) how to utilize the community as a quality supporter of the Laboratory of the Faculty of Ushuluddin, Adab, and Humanities IAIN Jember and (2) what are the results of the use of the community to support the quality of the Laboratory of the Faculty of Ushuluddin, Adab, and Humanities IAIN Jember. The method used in this research is descriptive qualitative with primary sources through observation and interviews and secondary sources through institutional laboratory profiles and village profiles. The informants in this study were the Dean and the Head of Study Programs within the Faculty of Ushuluddin, Adab, and Humanities, village officials, religious leaders, youth leaders, community leaders, and managers of tourism awareness groups. Data analysis was carried out through data categorization, data presentation, and concluding. The results of this study indicate (1) as an effort to support the quality of the Laboratory of the Faculty of Ushuluddin, Adab and Humanities IAIN Jember several communities are invited to work together, namely the Tourism Awareness Group (Pokdarwis), Youth Organizations and Muslimatan Studies. (2) The results of the utilization of the community to support the quality of the Laboratory of the Faculty of Ushuluddin, Adab, and Humanities IAIN Jember, namely being able to support student skills in the research carried out.